Seals and sealing in the Ancient world : case studies from the Near East, Egypt, the Aegean, and South Asia - Ameri, Marta, 1973- (Cambridge : Cambridge University Press, 2018)
Studies of seals and sealing practices have traditionally investigated aspects of social, political, economic, and ideological systems in ancient societies throughout the Old World. Previously, scholarship has focused on description and documentation, chronology and dynastic histories, administrative function, iconography, and style. More recent studies have emphasized context, production and use, and increasingly, identity, gender, and the social lives of seals, their users, and the artisans who produced them. Using several methodological and theoretical perspectives, this volume presents up-to-date research on seals that is comparative in scope and focus. The cross-cultural and interdisciplinary approach advances our understanding of the significance of an important class of material culture of the ancient world. The volume will serve as an essential resource for scholars, students, and others interested in glyptic studies, seal production and use, and sealing practices in the Ancient Near East, Egypt, Ancient South Asia and the Aegean during the 4th-2nd Millennia BCE.
Introduction: small windows, wide views / editors: Ameri, Costello, Jamison, Scott -- Part I. The Ancient Near East & Cyprus -- Administrative role of seal imagery in the early Bronze Age: Mesopotamian and Iranian traders on the plateau / Holly Pittman -- Slave labor: Uruk cylinder seal imagery and early writing / Sarah Jarmer Scott -- The first female bureaucrats: gender and glyptic in 4th-3rd millennia Northern Mesopotamia / Andrew McCarthy -- Rematerializing the early dynastic banquet seal / Sarah Kielt Costello -- Sealing practices in the Akkadian Period / Yelena Z. Rakic -- Authenticity, seal recarving, and authority in the Ancient Near East and Eastern Mediterranean / Joanna Smith -- Part II. South Asia and Persian Gulf -- Indus seals and glyptic studies: an overview / Asko Parpola -- Letting the pictures speak: an image-based approach to the mythological and narrative imagery of the Harappan world / Marta Ameri -- Understanding Indus seal carving traditions: a stylistic and metric approach / Gregg M. Jamison -- Operational sequences and stamp seals: a new approach to identifying groups of seal carvers in the Indus civilization / Adam Green -- Seals and sealing technology in the Dilmun Culture: the post Harappan life of the Indus Valley sealing tradition / Steffen Laursen -- Part III. Egypt -- The evolution of ancient Egyptian seals and sealing systems / Joe Wegner -- Early dynastic sealing practices as reflection of state formation in Egypt? / Ilona Regulski -- Sealings and seals from pyramid age Egypt / John Nolan -- The administrative use of scarabs during the Middle Kingdom / Daphna Ben Tor -- Middle and New Kingdom sealing practice in Egypt and Nubia: a comparison / Stuart Tyson Smith -- Part IV. Aegean -- Introductory remarks, Aegean / Judith Weingarten -- Aegean Bronze Age sealstones and fingerrings: chronology and functions / John Younger -- An Aegean seal in Greek hands? Thoughts on the perception of Aegean seals in the Iron Age / Maria Anastasiadou -- Cryptic glyptic: multivalency in Minoan glyptic imagery / Erin Mcgowan -- The magic and the mundane: the function of talismanic class stones in Minoan Crete / Angela Murock Hussein.
Title from publisher's bibliographic system (viewed on 24 Apr 2018).
Keywords: Cylinder seals; Seals (Numismatics); Public administration -- History